Evaluation of Some Specific Primer Sets Development for Detecting Fusarium oxysporum f. sp. cubense Tropic Race 4 (Foc TR4) Originating from Indonesia - Yudha Pratama; Arif Wibowo; Ani Widiastuti; Siti Subandiyah; Sri Widinugraheni; Martijn Rep (Jurnal Perlindungan Tanaman Indonesia, 2018)
Fusarium oxysporum f. sp. cubense tropic race 4 (Foc TR4) strain which belong to Vegetative Compatibility Group (VCG) 01213 is the most devastating disease in global banana production. Validation of specific primer sets using the positive control (Foc TR4). In total, 50 isolates of Foc are collected from several banana production regions in Indonesia represent the group of VCG, races, genotype, cultivars, which are confirmed as Foc based on the tested using FocEf3 primer set, except Cjr-2 and Lmp-4 isolates. Foc-1/Foc-2 could amplify 34 Foc isolates included in Foc race 4. Three specific primer sets i.e. TR4-F/TR4-R, Six-1c, and TR4-F2/TR4-R1 are used to classify Foc isolates into Foc tropic race 4. TR4-F/TR4-R is known have the highest specificity as it could amplify 35 Foc isolates including positive controls (Foc TR4) compared to the other primer sets (Six-1c and TR4-F2/TR4-R1). This research indicates that there are a large number of diversity strains found in Foc isolates to be studied for further research. Race 4 of Foc (STR4 or TR4) is known to be widespread in several regions in Indonesia. Therefore, specific primer set development needs to be done to detect Foc TR4 and the most damaging strains on Foc TR4 based on molecular data.IntisariFusarium oxysporum f. sp. cubense ras 4 tropika (Foc TR4) yang termasuk ke dalam kelompok VCG 01213 merupakan patogen yang paling merusak dalam produksi tanaman pisang secara global. Validasi primer spesifik berbasis PCR menggunakan kontrol positif (Foc TR4). Total, 50 isolat Foc dikoleksi dari  beberapa daerah produksi pisang di Indonesia mewakili VCG, ras, genotipe dan kultivar yang dikonfirmasi sebagai isolat Foc berdasarkan pengujian menggunakan primer FocEf3, kecuali isolat Cjr-2 dan Lmp-4. Foc-1/Foc-2 dapat mengamplifikasi 34 isolat Foc yang termasuk ke dalam Foc ras 4. Selanjutnya tiga pasang primer spesifik yaitu TR4-F/TR4-R, Six-1c, dan TR4-F2/TR4-R1 digunakan untuk mengelompokkan isolat-isolat tersebut ke dalam isolat Foc ras 4 tropika. TR4-F/TR4-R diketahui memiliki spesifitas tertinggi karena dapat mengamplifikasi sebanyak 35 isolat Foc termasuk kontrol positif (Foc TR4) dibandingkan dengan primer lainnya (Six-1c dan TR4-F2/TR4-R1). Penelitian ini menunjukkan bahwa terdapat sejumlah besar keragaman strain yang terlihat pada isolat-isolat Foc tersebut untuk dapat dipelajari lebih lanjut. Ras 4 dari Foc (STR4 atau TR4) diketahui tersebar luas pada beberapa daerah di Indonesia. Oleh karena itu, perlu dilakukan pengembangan primer spesifik untuk mendeteksi Foc TR4 dan strain yang paling merusak pada Foc TR4 berdasarkan data molekuler.